Glutathione S-Transferase Mu 1 and Glutathione S-transferase theta 1 Genes Polymorphism and Susceptibility to Chronic Myeloid Leukemia in Erbil-Iraq Kurdistan Region - Mukhlis H. Aali; Govand M. Qader; Mustafa S. Al-Attar; Mustafa F. Rajab; Mudhir S. Shehka (Zanco Journal of Pure and Applied Sciences, 2020)
Chronic myeloid leukemia (CML) result from many reactions of heredity non-heredity factors. The null genotype for glutathione S-transferase (GSTM1 or GSTT1) is regarded a risk agent leukemia, especially on CML in various inhabitants. The current study focused on evaluating association of two polymorphic identified genes Glutathione S-Transferase Mu 1 and glutathione S-transferase null genotypes that respect to CML patients from Erbil province, hence this work was performed a case-control study that composed of 51 samples (62% males, 39% females) with CML included and 45 healthy controls (22% male and 78% females) have participated. Multiplex PCR was used to ascertain GSTM1 and GSTT1 null genotypes. The chi-square test was done to show any link between GSTM1 and GSTT1 null genotypes that might be occurred in CML. There are significant statistical differences between incidence of GSTM1 null genotypes among CML cases and the increased CML risk was showed in patients bearing any of the GSTM1 null genotypes (OR = 2.196, 95%CI = (0.6017-6.806), P-value = 0.2108). While there is no statistical relation of GSTT1 null genotype with the risk of CML and exhibited lower risk initiation of CML occurrence (OR: 0.391, 95% CI: 0.1741-0.9033, P-value = 0.0304). Our findings demonstrate that GSTM1 null genotype is linked with the risk of CML patient development. The statements are helpful for formulating different investigation including GSTM1, GSTT1 variation genes and comparing research outputs with geography zone diverse in Iraq.